The integrative fundamentals of alexithymia - L. A. Severyanova; B. B. Plotnikov; D. B. Plotnikov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The aim of the study was to show the interrelation between the gradually increasing alexithymia traits and the integrative self regulation style of emotional, personal and cognitive interaction with the environment. The Toronto Alexithymia scale was used for examination of 356 students of a medical university. The students were divided into 4 groups in accordance with the alexithymia degree (69 - 94 scores for a high degree). The integral methods of estimation of an individuality were: Temperament Traits Accentuation, Differential estimation of Personal anxiety, Property Concept Discrimination and Copying Strategy. We noticed that the higher was the alexithymia degree the more marked was accentuation of asthenic temperament traits (emotional instability, social and objective passivity) and of personal anxiety (neural-psychic excitability and shyness). There was prevalence of inadaptive copying strategies and abstractive self-controlling style of intellectual activity. Alexithymia is the integral psychological phenomenon combining emotional, volutional, personal and mental parameters of an individuality as a whole. The structure of the phenomenon allows existence of different variants of the components and hence of its typology - the fact of scientific and practical value.